2007
DOI: 10.1002/per.614
|View full text |Cite
|
Sign up to set email alerts
|

Right wing authoritarianism, social dominance orientation and the dimensions of generalized prejudice

Abstract: Prior research suggests that individuals' prejudiced attitudes form a single generalized dimension predicted by Right Wing Authoritarianism (RWA) and Social Dominance Orientation (SDO). A dual process approach, however, expects different domains of generalized prejudice that relate differentially to RWA and SDO. To test this, 212 participants rated attitudes to 24 typically disliked groups. Factor analysis revealed three distinct generalized prejudice dimensions. Hierarchical Linear Modelling indicated that at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
464
5
42

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 420 publications
(543 citation statements)
references
References 32 publications
32
464
5
42
Order By: Relevance
“…Finally, a growing body of research on generalized prejudice has shown that individuals who hold negative attitudes towards a particular ethnic group also tend to be less favourable towards other ethnic groups, and even towards other minority groups that are not based on ethnicity (e.g., Akrami, Ekehammar, and Bergh 2011;Duckitt and Sibley 2007;McFarland 2010;see also, Allport 1954), as such supporting the use of measures referring to immigrants as a single group for the purpose of our study. Nevertheless, future studies might focus on individual immigrant groups concentrated in specific areas, considering how the distribution of specific minority groups relates to group-specific attitudes (e.g., Fleischmann et al 2012).…”
Section: Implications and Directions For Future Researchmentioning
confidence: 91%
“…Finally, a growing body of research on generalized prejudice has shown that individuals who hold negative attitudes towards a particular ethnic group also tend to be less favourable towards other ethnic groups, and even towards other minority groups that are not based on ethnicity (e.g., Akrami, Ekehammar, and Bergh 2011;Duckitt and Sibley 2007;McFarland 2010;see also, Allport 1954), as such supporting the use of measures referring to immigrants as a single group for the purpose of our study. Nevertheless, future studies might focus on individual immigrant groups concentrated in specific areas, considering how the distribution of specific minority groups relates to group-specific attitudes (e.g., Fleischmann et al 2012).…”
Section: Implications and Directions For Future Researchmentioning
confidence: 91%
“…En segundo lugar, se observó que al igual que en estudios previos (Asbrock et al, 2010;Duckitt y Sibley, 2007), el modelo de tres dimensiones correlacionadas del prejuicio generalizado indicó un mejor ajuste a los datos de la muestra que el modelo de una dimensión. Además, luego de analizar las asociaciones entre cada una de estas dimensiones, se observó que las mismas son significativas entre "Grupos Peligrosos" y "Grupos Disidentes", así como entre "Grupos Derogados" y "Grupos Disidentes", no hallándose asociaciones significativas entre "Grupos Peligrosos" y "Grupos Derogados".…”
Section: Discussionunclassified
“…Por el contrario, es necesario analizar la independencia de estas variables como predictoras del prejuicio generalizado, a partir del rol subyacente a nivel motivacional de la percepción de ciertos grupos como peligrosos, derogados o disidentes (Duckitt, 2001;Duckitt y Sibley, 2007).…”
Section: Discussionunclassified
See 2 more Smart Citations